Mixed Mating in a Multi-Origin Population Suggests High Potential for Genetic Rescue in North Island Brown Kiwi, Apteryx mantelli - Undin, Malin; Lockhart, Peter J.; Hills, Simon F. K.; Armstrong, Doug P.; Castro, Isabel (Frontiers in Conservation Science, 2021)
Reinforcement translocations are increasingly utilised in conservation with the goal of achieving genetic rescue. However, concerns regarding undesirable results such as genetic homogenisation or replacement are widespread. One factor influencing translocation outcomes is the rate at which the resident and the introduced individuals interbreed. Consequently, post-release mate choice is a key behaviour to consider. Here we studied mating and its consequences for genomic admixture in the North Island brown kiwi Apteryx mantelli population on Ponui Island which was founded by two translocation events over 50 years ago. The two source populations used are now recognised as belonging to two separate management units where birds differ in size and are genetically differentiated. We examined the correlation between male and female morphometrics for 17 known pairs and quantified the relatedness of 20 pairs from this admixed population. In addition, we compared the genetic similarity and makeup of 106 Ponui Island birds, including 23 known pairs, to birds representing the source populations for the original translocations. We found no evidence for size-assortative mating. On the contrary, genomic SNP data suggested that kiwi of one feather did not flock together, meaning that mate choice resulted in pairing between individuals that were less related than expected by random chance. Furthermore, the birds in the current Ponui Island population were found to fall along a gradient of genomic composition consistent with non-clustered representation of the two parental genomes. These findings indicate potential for successful genetic rescue in future Apteryx reinforcement translocations, a potential that is currently underutilised due to restrictive translocation policies. Thus, we suggest that reconsideration of these policies could render great benefits for the future diversity of this iconic genus in New Zealand.